2011
DOI: 10.1101/lm.2283011
|View full text |Cite
|
Sign up to set email alerts
|

Running is the neurogenic and neurotrophic stimulus in environmental enrichment

Abstract: Environmental enrichment (EE) increases dentate gyrus (DG) neurogenesis and brain-derived neurotrophic factor (BDNF) levels. However, running is considered an element of EE. To dissociate effects of physical activity and enrichment on hippocampal neurogenesis and BDNF levels, young female C57Bl/6 mice were housed under control, running, enrichment, or enrichment plus running conditions, and injected with bromodeoxyuridine. Cell genesis was assessed after 12 d and differentiation was analyzed 1 mo later. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
253
1
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(288 citation statements)
references
References 32 publications
19
253
1
10
Order By: Relevance
“…APP SWE /PS-1 E9 mice which were housed under environmental enrichment conditions from two months of age to 8.5 months old surprisingly displayed an exacerbated amyloid pathology compared to their counterparts housed under standard conditions (Jankowsky et al, 2003). This finding could be explained however by the low ratio of running wheels to mice in the cage, which is in line with more recent work from the van Praag laboratory highlighting the importance of the running wheel in the enriched environment (Kobilo et al, 2011). Subsequent studies reported an amelioration in amyloid pathology in APP SWE /PS-1 E9 mice and improvements in cognitive function in the APP SWE mice housed in an enriched environment (Arendash et al, 2004;Lazarov et al, 2005) Building upon these data, studies have also investigated the use of exercise exclusively in mouse models of AD and have made some interesting observations.…”
Section: The Benefits Of Exercise In Mouse Models Of Adsupporting
confidence: 78%
See 3 more Smart Citations
“…APP SWE /PS-1 E9 mice which were housed under environmental enrichment conditions from two months of age to 8.5 months old surprisingly displayed an exacerbated amyloid pathology compared to their counterparts housed under standard conditions (Jankowsky et al, 2003). This finding could be explained however by the low ratio of running wheels to mice in the cage, which is in line with more recent work from the van Praag laboratory highlighting the importance of the running wheel in the enriched environment (Kobilo et al, 2011). Subsequent studies reported an amelioration in amyloid pathology in APP SWE /PS-1 E9 mice and improvements in cognitive function in the APP SWE mice housed in an enriched environment (Arendash et al, 2004;Lazarov et al, 2005) Building upon these data, studies have also investigated the use of exercise exclusively in mouse models of AD and have made some interesting observations.…”
Section: The Benefits Of Exercise In Mouse Models Of Adsupporting
confidence: 78%
“…While there is still much focus on the signalling mechanisms by which exercise effects are mediated, upregulation of the neurotrophin brain-derived neurotrophic factor (BDNF) has been consistently reported following exercise interventions. Increased expression of hippocampal BDNF and its receptor TrkB has been observed following voluntary wheel running (Gibbons et al, 2014;Kobilo et al, 2011;Marlatt et al, 2012) and forced treadmill exercise Griffin et al, 2009;Wu et al, 1985). At a behavioural level, improvements in spatial learning and memory, associative learning and recognition memory have all been observed in animals following exercise training.…”
Section: Adult Hippocampal Neurogenesis and Exercisementioning
confidence: 82%
See 2 more Smart Citations
“…In a relevant study, Kobilo et al (2011) investigated the effects of physical activity in EE and concluded that this environment can promote some benefits to the organism such as the increase of brain derived neurotrophic factor (BDNF).…”
Section: Introductionmentioning
confidence: 99%